Decarbonising electricity made simple - Crossland, Andrew F. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This book assesses how low-carbon generation, the advance of energy storage and consumer-based models can help decarbonise electricity supplies at a national level. This book is built around developing a decarbonised electricity mix for Britain which reduces fossil fuels from 50% of supply in 2018 down to levels within 2030 carbon targets. Crossland explores the idea of a future energy storage mix which blends domestic batteries, vehicles, thermal stores and pumped hydro to provide a flexible, responsive electricity system. He then goes on to look at how much storage can contribute to decarbonisation in a multitude of contexts - from domestic to national electricity. This book also discusses how efficiency and self-sufficiency can bring about a decarbonised electricity use within our homes today. Britain is used as the main example, but the themes and conclusions are applicable to a global audience, and each chapter draws on practical case studies from around the world to illustrate key ideas. Drawing on the author's experience in delivering and analysing low-carbon energy projects in the UK, Sub-Saharan Africa, Latin America and Oceania, this book will be of great relevance to students, scholars and industry specialists with an interest in energy technology, policy and storage.
Change is normal in Britain's evolving and decarbonising electricity system -- Designing a low carbon electricity system -- Welcome to the store-age : the energy storage mix and its role in flexible electricity -- What makes new energy so different? -- A vision for decarbonising British electricity -- A vision for lower carbon domestic electricity -- Continuing the decarbonisation of energy.
OCLC-licensed vendor bibliographic record.
Keywords: Electric power production -- Technological innovations; Renewable energy sources; Carbon dioxide mitigation; Electric power-plants -- Fuel; TECHNOLOGY / Electricity; TECHNOLOGY / Environmental Engineering & Technology